Models for short fruits' chain - Andreea Ion Raluca (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The paper presents models for short chains of fruits, considering integration as the main mechanism of coordination agents' activities on the chain. The research answer the question how efficient are activities of fruits' chain in this particular form of integrated activities of collecting fruits, store and process them in juices and jams and sell them to the market, in a single economic unit. The objective of the research is to assess the efficiency of such a business. In achieving this purpose, economic data regarding investment, production, revenues and expenses have been analysed, for an associative form of processing and selling fruits, which develops such a business. The results show that investment is feasible, because revenues are higher than expenses, the rate of return is 5%, and the return of investment is 5.66 years, less than the machineries' period of operation. The model is useful for farmers owning orchards, who want to apply for structural funds and to develop, as such, their business in the direction of integrating activities downstream the chain.
Keywords: Q13; 330; short chain; fruits; efficiency; integration